2018
DOI: 10.3389/fimmu.2018.02124
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine Inhibits Monomeric C-Reactive Protein Induced Inflammation, Endothelial Cell Adhesion, and Platelet Aggregation; A Potential Therapeutic?

Abstract: Objectives: In this study, we examined the possibility of using targeted antibodies and the potential of small molecular therapeutics (acetylcholine, nicotine and tacrine) to block the pro-inflammatory and adhesion-related properties of monomeric C-reactive protein (mCRP).Methods: We used three established models (platelet aggregation assay, endothelial leucocyte binding assay and monocyte inflammation via ELISA and Western blotting) to assess the potential of these therapeutics.Results: The results of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…CRP is known to affect innate immunity operating through the nicotinic acetylcholine receptors and here, Richter et al ( 9 ) showed that pCRP associated with phosphocholine, could block macrophage-induced cytokine release potentially protecting trauma-associated injuries in vivo . In contrast, mCRP potently stimulates macrophage-associated inflammation, and further work detailed in this series showed that acetylcholine inclusion, within an in vitro model of inflammation, could effectively block mCRP-induced production of tumor necrosis factor-alpha ( 10 ).…”
mentioning
confidence: 99%
“…CRP is known to affect innate immunity operating through the nicotinic acetylcholine receptors and here, Richter et al ( 9 ) showed that pCRP associated with phosphocholine, could block macrophage-induced cytokine release potentially protecting trauma-associated injuries in vivo . In contrast, mCRP potently stimulates macrophage-associated inflammation, and further work detailed in this series showed that acetylcholine inclusion, within an in vitro model of inflammation, could effectively block mCRP-induced production of tumor necrosis factor-alpha ( 10 ).…”
mentioning
confidence: 99%
“…The above findings have been later supported by experimental studies indicating that 1,6-bis-PC is able to prevent the dissociation of CRP and inhibit its deposition in inflamed tissue [101]. Very recently, acetylcholine and nicotine have been found to have beneficial effects on reducing mCRP-induced inflammatory events [102]. Taken together, these findings encourage further testing: more pharmacokinetic and pharmacodynamic data acquired by local and systemic approaches are required to determine whether these substances are suitable for clinical purposes.…”
Section: Pentameric C-reactive Proteinmentioning
confidence: 84%
“…Monomeric C-reactive protein was recently shown to directly exert a pro-inflammatory effect upon macrophages and glia, via induction of nitric oxide synthase ( 21 ) and TNF-α/IL-1β amongst other cytokines ( 22 ). Hence this could be a mechanism that could partially explain how the deposition of mCRP may support creation of a pro-inflammatory micro-environment perpetuating on going damage.…”
Section: Discussionmentioning
confidence: 99%
“…In regard to the possible relationship to angiogenesis, aberrant angiogenesis associated with formation of none-patent or leaky microvessels as part of a regenerative or restorative effort within damaged brain tissue only serves to permeabilise the parenchyma thereby further increasing immune cell infiltration and so on and so forth ( 2 , 22 ). It was recently shown that mCRP was able to disrupt the outer retinal blood brain barrier indicating a potential role in inflammatory macular degeneration ( 23 ), taken together, it appears that mCRP may have distinct effects both directly upon the vascular integrity and other pro-inflammatory stimulatory effects that combined could impact upon the normal function of the neurovascular unit.…”
Section: Discussionmentioning
confidence: 99%